Supplier assessment and selection using fuzzy analytic hierarchy process in a steel manufacturing company - Tahriri, F.; Dabbagh, M.; Ale Ebrahim, N. (Sciencedomain international., 2014)
Every organization needs suppliers and no organization can exist without suppliers. Therefore, the organizations approach to suppliers and the selection of the appropriate supplier, its acquisition processes and policies, and its relationships with suppliers, is of vital importance, both to organizations and suppliers alike. No organization can be successful without the support of its supplier base, operationally and strategically, short or long-term.To select the best supplier, it is essential to make an analytical decision based upon tangible and intangible criteria. Chose and management of a supplier has to be congruent with organizational strategy. Therefore, the vision and strategy of the manufacturer are the key drivers for how the supply function will be managed and how supply decisions are made and exectuted. The proposed model in this study was applied in a steel manufacturing company in Malaysia with the goal of reducing time in choosing the correct supplier for the company. This study aims to provide a systematic model stimulating correct supplier selection using the Fuzzy Analytic Hierarchy Process (FAHP) method along with a series of sensitivity analyses which were conducted using the Expert Choice (EC) program to evaluate the impact of changes in the priority of criteria for the suppliers' performance and order quantities. Aims: The main goal of this research is to develop a systematic model towards the best supplier selection. To facilitate the aim of the research, we utilized the Fuzzy Analytic Hierarchy Process, which was a combination of AHP and Fuzzy Theory in order to deal with the uncertainties and vagueness of decision makers's judgement. Study Design: Mention the design of the study here. Place and Duration of Study: The data samples were taken in a steel manufacturing company in Malaysia. Methodology: A Fuzzy Analytic Hierarchy approach is used using a quantitative and qualitative criteria for selecting and evaluating a suitable supplier selection and a six step was conducted to ensure successful implementation. Results: The results indicate that the model is able to assist decision makers to examine the strengths and weaknesses of supplier selection by comparing them with appropriate criteria, sub-criteria and sub sub-criteria. Conclusion: We developed a Fuzzy AHP multi-criteria decision making model for supplier evaluation and selection in the ABC steel company in Malaysia. The advantage of the proposed model over other models like the AHP is that, by adoption of fuzzy numbers, it effectively improves the flexibility of the conventional AHP in dealing with the uncertainty and ambiguity associated with different decision makers's judgments.